Financial literacy on the financial management of MSME actors in Makassar City - Sudirman Sultan; Al Kausar; Feronica Fungky Muchsidin (Institute of Computer Science (IOCS), 2023)
MSME actors must possess financial management skills and financial literacy to boost their business performance. This study intends to identify the partial and simultaneous effects of basic and advanced financial literacy on the financial management of MSME actors in Makassar City. The offspring of this study are the 100 MSME actors in Makassar City who made up the investigated samples. Data analysis with the use of the SmartPLS software. Testing of physiological variables' hypotheses P values of 0.047 < 0.05 indicate that basic financial literacy variables have a positive and significant impact on financial management, while P values of 0.000 < 0.05 indicate that advanced financial literacy variables have a positive and significant impact on financial management. The R square value of 0.664 indicates that both basic and advanced financial literacy variables positively and significantly impact financial management. The analysis's findings revealed that the basic financial literacy variable had a major influence of 25.4%, the advanced financial literacy variable had a major influence of 59.9%, and other variables that were not measured in this study were responsible for the remaining influences on financial management. Based on the findings of this study, it can be inferred that to enhance their financial management abilities and boost business performance, MSMEs should prioritize improving their financial literacy. This can be achieved by increasing their understanding and knowledge of financial matters.